Law No. 8 of the year 2022 Promulgating The Hotel And Tourist Establishments Law = قانون رقم 8 لسنة 2022 بشأن إصدار قانون المنشآت الفندقية والسياحية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic